2018
DOI: 10.1175/jhm-d-18-0017.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Drought in Europe: A Compound Event of Precipitation and Potential Evapotranspiration on Multiple Time Scales

Abstract: Compound events are extreme impacts that depend on multiple variables that need not be extreme themselves. In this study, we analyze soil moisture drought as a compound event of precipitation and potential evapotranspiration (PET) on multiple time scales related to both meteorological drought and heat waves in wet, transitional, and dry climates in Europe during summer. Drought indices that incorporate PET to account for the effect of temperature on drought conditions are sensitive to global warming. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 60 publications
(86 reference statements)
3
87
0
Order By: Relevance
“…Simple correlations between monthly precipitation, temperature, PET, and soil moisture (not shown) support the conclusions of Manning et al (2018) on the influence of precipitation and PET on soil moisture at dry sites. They found that at waterlimited sites the influence of precipitation on soil moisture is much larger than the influence of temperature, via PET, on soil 20 moisture.…”
supporting
confidence: 53%
“…Simple correlations between monthly precipitation, temperature, PET, and soil moisture (not shown) support the conclusions of Manning et al (2018) on the influence of precipitation and PET on soil moisture at dry sites. They found that at waterlimited sites the influence of precipitation on soil moisture is much larger than the influence of temperature, via PET, on soil 20 moisture.…”
supporting
confidence: 53%
“…The results may also have implications for the persistence of soil moisture drought conditions. High amounts of precipitation are required for recovery from large moisture deficits induced by intense drying , Manning et al 2018 while general increases in evaporation can push environments towards a climatically drier state (Samaniego et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The joint occurrence of extremely long-duration and high magnitude events may thus lead to higher soil moisture deficits than events where only one characteristic is extreme. Larger deficits can produce longer lasting soil moisture droughts as higher amounts of precipitation are then required for drought recovery , Manning et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect effects are more important given that under unlimited soil water content more AED usually means more plant transpiration. These hydrological effects are usually complex since they depend on the runoff generation processes and the length of the dry period, but more ET will generally reduce soil moisture (Manning et al, ; Teuling et al, ). This AED effect could propagate throughout other parts of the hydrological cycle and cause a streamflow reduction (Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, LĂłpez‐Moreno, et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, MorĂĄn‐Tejeda, et al, ; Vicente‐Serrano, Lopez‐Moreno, et al, ).…”
Section: The Complex Influence Of Aed On Drought Severitymentioning
confidence: 99%